In vitro anti-proliferative mechanism of combination therapy with tannic acid and cisplatin against human osteosarcoma cell line U2OS - Kasiram, Mohamad Zahid Mohd (2024)
Osteosarcoma is most common primary bone malignancy that affects children and young adults. The survival rate remains low, especially in metastatic cases. Tannic acid (TA), a phenolic compound found in medicinal plants, has shown promising efficacy in enhancing chemotherapeutic drugs against various cancers. Hence, this study aimed to investigate the effect of TA treatment combined with cisplatin on human osteosarcoma cell line (U2OS). The half-maximal inhibitory concentration (IC50) values of TA and its combination with cisplatin against U2OS cells were determined using MTT assay. MTT assay also assessed TA cytotoxicity on normal human foetal osteoblast (hFOB 1.19) cell line. The pharmacological interaction between TA and cisplatin was evaluated using CompuSyn software. The anti-proliferative activity was evaluated by using trypan blue exclusion assay. The morphological and ultramorphological alteration of the U2OS cells were examined using phase contrast inverted microscope and scanning electron microscope (SEM), respectively. The nuclear morphological changes were evaluated by Hoechst 33258 nuclear staining and observed under fluorescence microscope. The percentage of apoptotic cells was measured using flow cytometer after conducting annexin V/propidium iodide (PI) assay. A mechanistic study was conducted by evaluating mRNA expression of mitogen-activated protein kinase (MAPK) and apoptotic pathway using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). The IC50 values of TA and cisplatin were determined at 4.47 and 16.25 μg/mL, respectively. TA induced no significant inhibitory effect on hFOB 1.19 cells, but potent proliferative effect was indicated. The combination of TA with cisplatin at percentage ratios of 90:10 and 85:15 induced synergistic interaction, while the combination at 75:25 and 50:50 induced antagonistic interaction. The combination at 90:10 showed the highest potency with the lowest IC50 value at 3.56 μg/mL. A significant anti-proliferative effect with prominent morphological and ultramorphological alteration was detected in the combination-treated cells. The cells appeared shrunk, with blebbed membrane and reduced appearance of lamellipodia and filopodia. Additionally, prominent nuclear morphological alteration and highest percentage of apoptotic cells were noted in the combination-treated cells. RT-qPCR analysis indicated the significant upregulation of ERK2, BAX, caspase-9, and caspase-3 and downregulation of JNK1 and BCL2 mRNA expression in the TA- and combination-treated cells. Mechanistically, anti-proliferative and apoptotic effect of TA and its combination with cisplatin on U2OS cells were suggested to be modulated via JNK1 inhibition, ERK2 activation, and intrinsic apoptotic pathways. The findings suggest the potential inclusion of TA in cisplatin-based chemotherapy for osteosarcoma and warrant further investigation